Roman and Briton women from Britannia (Heródoto: Revista do Grupo de Estudos e Pesquisas sobre a Antiguidade Clássica e suas Conexões Afro-asiáticas, 2018)
The purpose of this article is to reflect on women from the ancient society and their studies, especially from Britannia. This work is made up of Romans and Britons women, who composed different costumes, which interspersed, which lived there and which were in some way evidenced by written and/or material vestiges. This was not a homogenous group, both for the population that had already lodged there and for the one that came later, there was a great variety of ideas about their status and how they should lead their lives. Materials on Roman and Briton have already been found epigraphically, on altars, tombstones and burials. However, this work will compare these first sources with the work of Tacitus, Annals, since this author always seems to place women with pejorative characteristics, very different from the loving and amorous words given to them in these places of death.